Perivascular Adipose-Derived Exosomes Reduce Foam Cell Formation by Regulating Expression of Cholesterol Transporters - Liu, Yan; Sun, Yan; Lin, Xuze; Zhang, Dai; Hu, Chengping; Liu, Jinxing; Zhu, Yong; Gao, Ang; Han, Hongya; Chai, Meng; Zhang, Jianwei; Zhou, Yujie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Accumulating evidence demonstrates that perivascular adipose tissue (PVAT) plays an important role in maintaining vascular homeostasis. The formation of macrophage foam cells is a central feature of atherosclerosis. This study aimed to evaluate the effect of PVAT-derived exosomes (EXOs) on the lipid accumulation of macrophages and verify the anti-atherogenic characteristics of PVAT. Methods and Results: We extracted EXOs from the PVAT and subcutaneous adipose tissue (SCAT) of wild-type C57BL/6J mice. After coincubation, the EXOs were taken up by RAW264.7 cells. Oil Red O staining revealed that macrophage foam cell formation and intracellular lipid accumulation were ameliorated by PVAT-EXOs. Flow cytometry showed that PVAT-EXOs significantly reduced macrophage uptake of fluorescence-labelled oxidised low-density lipoprotein (ox-LDL). In addition, high-density lipoprotein-induced cholesterol efflux was promoted by PVAT-EXOs. Western blot analysis showed the downregulation of macrophage scavenger receptor A and the upregulation of ATP-binding cassette transporter A1 and ATP-binding cassette transporter G1, which could be mediated by the overexpression of peroxisome proliferator-activated receptor γ and was independent of liver X receptor α. Conclusion: Our findings suggest that PVAT-EXOs reduce macrophage foam cell formation by regulating the expression of cholesterol transport proteins, which provides a novel mechanism by which PVAT protects the vasculature from atherosclerosis.